The Impact of Cartoon Films and Technological Games on the Creed of a Muslim Child, an Analytical Study: تأثير الأفلام الكرتونية والبرامج التكنولوجية على عقيدة الطفل المسلم، دراسة تحليلية - Muhammad Abdoh, Muhammad Alsayyid (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
هدفت الدراسة إلى إبراز خطورة الرسوم المتحركة والألعاب التكنولوجية؛ خاصة على عقيدة الطفل المسلم والتي تؤثر تباعًا على سلوكه اجتماعيا ونفسيًا وثقافيًا، وقد تم الاعتماد على المنهج التحليلي في عرض نماذج من هذه الرسوم والألعاب، ومدى تأثيرهما عليه. وتأتي إشكالية البحث في أن هذه الألعاب والرسوم نشأت في بيئة غير إسلامية-مناسبة لها- ثم انتشرت بعد ذلك إلى الدول الإسلامية حاملة معها أفكارًا وسلوكيات؛ لكنها مخالفة لعقيدة الطفل المسلم، مما كان لها تأثير على عقلية المسلم صغيرًا أو كبيرًا، وأصبح العلماء يختلفون في حكم هذه الرسوم والألعاب، نظرًا لتأثيرهما إيجابيا وسلبيًا. وقد أظهرت النتائج أن هذه الرسوم المتحركة والألعاب الإلكترونية تعد من النوازل العقدية المعاصرة التي ينبغي إظهار الحكم الشرعي فيها بما يتناسب مع هذه النازلة، والالتزام بالضوابط التي لا تخالف شرع الله تعالى. الكلمات المفاتيح: العقيدة، النوازل، الأفلام الكرتونية، الألعاب الإلكترونية. Abstract The research aims at recognizing the danger of animation and Technological games, especially on the Muslim child’s Creed which in turn affect his social, psychological, and cultural behavior. The analytical method has been used to display examples of these games and animation and their influence. The dilemma of the research is that such games and animation have been created in a non-muslim environment then spread in the Islamic countries in cluding ideas and behaviors suitable for them, but they are contrary to the muslim child’s creed which has an influence on the young or old muslim’s mentality. The Sharia scholars disagree on the issue of these games and animation whether they affect negatively or positively. The results showed that these electronic games and animation are among the contemporary doctrinal catastrophes in which the injunction of Sharia should be shown in proportion to such catastrophe and adherence to the dictums that do not violate the law of God Almighty. Keywords: creed, catastrophe, animation, electronic games.